Corruption in healthcare services and the game theory model - Evaggelia Andreadaki; Athena Kalokairinou-Anagnostopoulou (Ene, 2018)
Introduction: It is intelligentia communis that Healthcare services, worldwide, suffer from corruption, thereby disrupting the social web of protection of the most important good, which is health. The Game Theory (GT), applied in situations of social dilemmas, highlights issues of personal benefits prioritization that eventually end up at the expense of the total as well as the individual. Aim: The aim of the present study was to explore corruption in the Greek healthcare services, to highlight its underlying causes, to record the socio-economic impact in the light of the GT. In addition the paper aims at highlighting the prevention and coping policies of this major problem. Μethods: An extensive literature review was conducted in various databases, such as "PubMed/ Medline", "Embase", "Cinahl", "Cochrane", in websites of various international organizations, Greek and foreign institutions, using, in Greek and English, key-words such as "corruption" , "fraud", "black economy", "Greek Health System", "Game Theory". The study included 195 publications, accepting finally those published in the last twenty-five years in Greek and English language. Results: Imoralisation of Healthcare Services is diminishing the principles of equality-accessibility- efficiency-effectiveness on which the modern Greek National Healthcare System (NHS) was built. Furthermore, it violates fundamental human rights. The amoralist activities involve all healthcare providers, are combined with a high level of general social corruption and have a direct, negative impact on the health status of Greek citizens, directly affecting the less privileged citizens. In recent years, healthcare system reforms have been structural and multilevel, with measures being taken to tackle and modify the actual background that has, overtime, nurtured corruption. Conclusions: Changing the citizens' philosophy and attitude against the phenomenon of corruption, is the key to determine the effectiveness of any measure taken. In a zero-sum game, confinement of healthcare partners to the exclusive claim of their individual/corporate interests acts as a coil of distortion of the wider social development and normality. The fight against corruption requires a transition to a new "Social Contract" with eagerness, resolute determination by political leaders, multi-sectoral interventions at legal/managerial level, and coordination of the efforts of all with a sense of esprit de corps.